Endothelial RBPJ is esential for the education of tumor-associated macrophages - Alsina Sanchis, Elisenda; Mülfarth, Ronja; Moll, Iris; Böhn, Sarah; Wiedmann, Lena; Jordana-Urriza, Lorea; Ziegelbauer, Tara; Zimmer, Eleni; Taylor, Jacqueline; De Angelis Rigotti, Francesca; Stögbauer, Adrian; Giaimo, Benedetto Daniele; et al. (Cancer research, 2022)
Epithelial ovarian cancer (EOC) is one of the most lethal gynecologic cancers worldwide. EOC cells educate tumor-associated macrophages (TAM) through CD44-mediated cholesterol depletion to generate an immunosuppressive tumor microenvironment (TME). In addition, tumor cells frequently activate Notch1 receptors on endothelial cells (EC) to facilitate metastasis. However, further work is required to establish whether the endothelium also influences the education of recruited monocytes. Here, we report that canonical Notch signaling through RBPJ in ECs is an important player in the education of TAMs and EOC progression. Deletion of Rbpj in the endothelium of adult mice reduced infiltration of monocyte-derived macrophages into the TME of EOC and prevented the acquisition of a typical TAM gene signature; this was associated with stronger cytotoxic activity of T cells and decreased tumor burden. Mechanistically, CXCL2 was identified as a novel Notch/RBPJ target gene that regulated the expression of CD44 on monocytes and subsequent cholesterol depletion of TAMs. Bioinformatic analysis of ovarian cancer patient data showed that increased CXCL2 expression is accompanied by higher expression of CD44 and TAM education. Together, these findings indicate that EOC cells induce the tumor endothelium to secrete CXCL2 to establish an immunosuppressive microenvironment.Endothelial Notch signaling favors immunosuppression by increasing CXCL2 secretion to stimulate CD44 expression in macrophages, facilitating their education by tumor cells.